Finding the Dividing Line Between Tax Sharing and Grants A Statistical Investigation - Blöchliger, Hansjörg (OECD Working Papers on Fiscal Federalism, 2009)
Tax sharing and intergovernmental grants are two sub-central funding arrangements that are often difficult to disentangle. The dividing line is not drawn uniformly across OECD countries or across time, and rules established in National Accounts, Revenue Statistics and others give incomplete guidance. Moreover, tax sharing arrangements may differ according to how tax revenue is distributed across individual jurisdictions. In order to ensure that fiscal arrangements are recorded properly and on a comparable basis, a set of clear criteria to delineate them is required. This section presents the results of a test that was applied in order to find the dividing line a) between tax sharing and intergovernmental grants and b) between different categories of tax sharing. The test was performed using questionnaire responses and builds on earlier documents on the same topic presented to Fiscal Network Delegates in 2006 and 2008